Rethinking Social Action through Music The Search for Coexistence and Citizenship in Medellín's Music Schools - Baker, Geoffrey (Open Book Publishers, 2021)
"How can we better understand the past, present and future of Social Action through Music (SATM)? This ground-breaking book examines the development of the Red de Escuelas de Música de Medellín (the Network of Music Schools of Medellín), a network of 27 schools founded in Colombia's second city in 1996 as a response to its reputation as the most dangerous city on Earth. Inspired by El Sistema, the foundational Venezuelan music education program, the Red is nonetheless markedly different: its history is one of multiple reinventions and a continual search to improve its educational offering and better realise its social goals. Its internal reflections and attempts at transformation shed valuable light on the past, present, and future of SATM. Based on a year of intensive fieldwork in Colombia and written by Geoffrey Baker, the author of El Sistema: Orchestrating Venezuela's Youth (2014), this important volume offers fresh insights on SATM and its evolution both in scholarship and in practice. It will be of interest to a very varied readership: employees and leaders of SATM programs; music educators; funders and policy-makers; and students and scholars of SATM, music education, ethnomusicology, and other related fields."